Online Damage Complaint Management System for Kolej Kediaman Tun Fatimah - Dahri, Nurul Atiqah; Mohd Yusof, Munirah (Applied Information Technology And Computer Science, 2024)
The advancement of digital technology has profoundly impacted how many traditional industries perform their daily functions. This project aims to develop a specialised system to address and rectify instances of general and electrical damage within the Universiti Tun Hussein Onn Malaysia (UTHM) residential facilities. The primary objective is to facilitate and expedite the residential college management’s ability to identify and respond to general and electrical damage issues among the students who stay there. The methodology used to develop this project is the agile methodology. It is because agile methodology prioritises cross-functional collaboration and continuous improvement. The expected outcome for this project is that implementing this system will help to make it easier for students to complain about the damage they face. In addition, changing traditional methods to digital methods will make it easier for management to manage data.